2009
DOI: 10.1186/1471-230x-9-50
|View full text |Cite
|
Sign up to set email alerts
|

The galactose elimination capacity and mortality in 781 Danish patients with newly-diagnosed liver cirrhosis: a cohort study

Abstract: Background: Despite its biologic plausibility, the association between liver function and mortality of patients with chronic liver disease is not well supported by data. Therefore, we examined whether the galactose elimination capacity (GEC), a physiological measure of the total metabolic capacity of the liver, was associated with mortality in a large cohort of patients with newlydiagnosed cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
2
23
0
2
Order By: Relevance
“…This novel finding expands upon our previous finding that the GEC is a predictor of the mortality of cirrhosis patients [3]: It is now clear that loss of hepatic metabolic capacity causes hepatic encephalopathy and then death [1]. Our previous study suggested that a GEC above 1.75 mmol/min was associated with a relatively favorable prognosis, whereas mortality increased linearly with GEC when GEC fell below this limit [3]. We speculate that the same limit applies to the risk of hepatic encephalopathy, but our current study did not have sufficient statistical power to clarify this.…”
Section: Discussionsupporting
confidence: 82%
“…This novel finding expands upon our previous finding that the GEC is a predictor of the mortality of cirrhosis patients [3]: It is now clear that loss of hepatic metabolic capacity causes hepatic encephalopathy and then death [1]. Our previous study suggested that a GEC above 1.75 mmol/min was associated with a relatively favorable prognosis, whereas mortality increased linearly with GEC when GEC fell below this limit [3]. We speculate that the same limit applies to the risk of hepatic encephalopathy, but our current study did not have sufficient statistical power to clarify this.…”
Section: Discussionsupporting
confidence: 82%
“…The hepatic removal of galactose follows Michaelis–Menten kinetics in vivo (27,40). The hepatic galactose elimination rate at near-saturating concentration, that is, the galactose elimination capacity, is used as a measure of metabolic liver function (41), with documented prognostic information for patients with liver diseases (42). However, the galactose elimination capacity does not provide any information on possible intrahepatic regional variations that are also clinically relevant and can be explored by PET…”
Section: Hepatic Metabolism Studied By Petmentioning
confidence: 99%
“…When corrected for the amount of galactose excreted in urine, an approximate estimate of the hepatic V max for galactose is achieved from the blood disappearance curve using blood concentrations ensuring near-saturation of the enzymatic system [1–4]. The GEC accurately assessed survival prognosis of patients with acute liver failure [5], chronic liver disease [6,7], and patients undergoing liver resection [8]. More interestingly, it has been shown that quantitative liver function tests such as the GEC are far more predictive of the remaining liver function following partial hepatectomy than measurements of liver volumes [911].…”
Section: Introductionmentioning
confidence: 99%